Athens & Jerusalem - Shestov, Lev, 1866-1938 (Ohio University Press, 2016)
For more than two thousand years, philosophers and theologians have wrestled with the irreconcilable opposition between Greek rationality (Athens) and biblical revelation (Jerusalem).